Retrospective Analysis of Scapula Posture Assessment in Patients with sub-acromial Impingement Syndrome in a Tertiary Care Hospital (Indian Journal of Physiotherapy and Occupational Therapy - An International Journal, 2021)
Background: Sub-acromial impingement syndrome is one of the commonest musculoskeletal disorders.Abnormal posture and scapula dyskinesis are considered major risk factors for developing shoulder pain.Methods: A retrospective cross-sectional study was carried out involving 68 participants. Scapula postureassessed using acromion to plinth distance, distance from T4 to medial border, distance from T7 to inferiorangle and observation was analyzed.Results: The affected side demonstrated a significantly greater acromion to plinth distance (affected side:6.71±1.27 cm, non-affected side: 6.0±1.3 cm, p
Keywords: Acromion to plinth distance, Scapula posture, Shoulder pain, Sub-acromial impingement syndrome